Muslim Women in the Modern World: Identity, Voice, and Adaptation - Isran, Keeta; Rattanarungsikul, Phuvanart (DEC Journal : Art and Design, 2025)
This qualitative research aims to examine the status and roles of Muslim women in contemporary society by analyzing their rights, duties, and attributes based on Islamic principles, which significantly influence the construction of identity and daily life practices. The study employs an arts-based research approach combined with cultural content analysis to explore how art functions as a medium for expressing the ideas of Muslim women concerning religion, culture, and identity. Findings reveal that in the context of globalization, Muslim women face challenges in balancing religious values with sociocultural transformations. Art becomes a vital tool for negotiating identity through diverse representations of Muslim women in both religious and social dimensions. This study addresses a research gap by highlighting the lack of in-depth analysis on the use of art as a cultural space for Muslim women, particularly in contexts of conflict and change. The analysis is framed by Feminism, Post-colonial Feminism, and Visual Culture theories to explain the mechanisms through which Muslim women negotiate gender and religious identity via contemporary art. The research not only reflects the transformation within Muslim societies but also demonstrates the potential of art as a communicative platform and a space for creating new meanings in the modern era.